TADHARRU’ DALAM QS. AL-A’RAF AYAT 55 DAN IMPLEMENTASINYA DALAM BERDOA (STUDI PENAFSIRAN M. QURAISH SHIHAB DALAM TAFSIR AL-MISBAH) - AJEMI, NURAISAH (Al-I'jaz: Jurnal Kewahyuan Islam, 2023)
AbstractThis research is motivated by the attention of the author who has studied and analyzed a book of tafsir, namely the book "Tafsir Al-Misbah" which has been compiled by M. Quraish Shihab. He is known as a mufassir of the modern archipelago in Indonesia who is very influential with his works. The type of research used in this research is library research, then the data collection method uses qualitative methods, and the interpretation method uses the Maudu'i method. The results of this research explain Tadharru' which is explained in detail in Islam based on the opinions of Islamic scientists and the Al-Misbah Tafsir Book, which in conclusion is, etymologically Tadharru' means humbling oneself and one's heart to Allah SWT, and in terminology it is a characteristic that with it, a person is able to maintain good relationships with others and is able to maintain the privilege of his relationship with God, so that a person does not easily disbelieve in others when there are differences in interpretations regarding Islamic law. Tadharru's attitude in praying to QS. Al-A'raf verse 55 in the implementation of daily life contributes to the quality of worship and spiritual life of a Muslim. This reflects faith and awareness of God's power and is a form of sincere devotion. By practicing Tadarru' consistently, a servant can lower himself to Allah and attain His merits and grace both in this world and in the hereafter.Keywords: Al-Misbah, Tafsir, Tadharru'